(untitled) (Gestão & Regionalidade, 2017)
This article aims to analyze the socio-economic development in the delimited area of Vale dos Vinhedos region, located in the cities of Bento Gonçalves, Garibaldi and Monte Belo do Sul, Rio Grande do Sul, Brazil, from the recognition of the geographical indication and the perspective of social actors involved in the process. It refers to a qualitative, descriptive research in a historical perspective, from the point of view of the involved subjects hemselves, such as wine producers, managers of local associations, representatives of the public power and technicians who have formatted the process of recognition of wines’ origin indication. The data were collected from questionnaires and interviews with the mentioned social actors. The results initially provided the concepts of development (local, endogenous), intellectual property and geographical indications, in order to ground this research, demonstrating the promotion of development in Vale dos Vinhedos by its region origin indication. In addition, this research analyzes the case of this region looking for showing the economic and social implications of this recognition about the development of Vale dos Vinhedos.